A história local no currículo em escolas públicas municipais de Porto Seguro – BA - Moufarreg, Fabiana Mércia Souto Stefano (2022)
The main objective of this work is to research the consequences of the implementation of Municipal Law nº 236/96 in Porto Seguro - BA in municipal schools in the urban region classified in the category of special and large size. The aforementioned Law of December 10, 1996 creates the discipline History of Porto Seguro (HPS) and establishes the obligation of its teaching in all public schools of basic education in the municipal. The object of the research is the teaching of Local History, understood here as the History of Porto Seguro, in its construction as an autonomous school discipline, its implementation, trajectory, political uses and appropriations for teaching practices. The procedures adopted are bibliographic and documentary research and interviews. Our investigation is based on the bibliography on the Teaching of History, especially Local History, on the discussions on Identity and Curricular Theory, the theoretical foundations that articulate the concepts of academic knowledge, teaching knowledge and school knowledge as well as the principles that guide the use of historical sources in the classroom. As a result of the research, we developed a didactic product that aims to assist the teaching practice in meeting the demands of Law No. a more effective organization of the sources and supports available for teaching in public elementary schools. We propose to work with the use of historical sources in the teaching of the subject as a strategy for teachers to overcome the limitations arising from a more traditional conception of teaching. The product is in a virtual media format - website - that works as a source bank for teaching the subject in schools and will be managed by us in a collaborative way by teachers and other researchers interested in the local theme in the municipality. With the initiative, we seek to encourage an attitude of interaction and collaboration between HPS teachers, the History curricular component as well as other professionals who are interested in the local theme in order to help the practice in the classroom.